Influence of molecular weight of chemically sulfated citrus pectin fractions on their antithrombotic and bleeding effects - Cipriani, Thales R; Gracher, Ana Helena P; de Souza, Lauro M; Fonseca, Roberto J C; Belmiro, Celso L R; Gorin, Philip A J; Sassaki, Guilherme L; Iacomini, Marcello (Thrombosis and haemostasis, 2009)
Evaluated were the anticoagulant and antithrombotic activities, and bleeding effect of two chemically sulfated polysaccharides, obtained from citric pectin, with different average molar masses. Both low-molecular-weight (Pec-LWS, 3,600 g/mol) and high-molecular-weight sulfated pectins (Pec-HWS, 12,000 g/mol) had essentially the same structure, consisting of a (1-->4)-linked alpha-D-GalpA chain with almost all its HO-2 and HO-3 groups substituted by sulfate. Both polysaccharides had anticoagulant activity in vitro, although Pec-HWS was a more potent antithrombotic agent in vivo, giving rise to total inhibition of venous thrombosis at a dose of 3.5 mg/kg body weight. Surprisingly, in contrast with heparin, Pec-HWS and Pec-LWS are able to directly inhibit alpha-thrombin and factor Xa by a mechanism independent of antithrombin (AT) and/or heparin co-factor II (HCII). Moreover, Pec-HWS provided a lower risk of bleeding than heparin at a dose of 100% effectiveness against venous thrombosis, indicating it to be a promising antithrombotic agent.